Evaluation of Methods for Estimation of Reference Evapotranspiration - Gupta, A.; Sarangi, A.; Singh, D. K.; Parihar, S. S. (Indian Journal of Hill Farming, 2016)
Reference evapotranspiration (ET0) plays a key role in irrigation systems design and agricultural water management under both irrigated and rainfed situations. This study was carried out with the objective to compare the performance of Energy-Balance, Aerodynamic, Penman, Priestley-Taylor and Stephen-Stewart methods for the hilly and plain regions of north India for estimation of reference evapotranspiration with data intensive Modified Penman-Monteith (PENMON) method using the daily weather data acquired from automatic weather station during 2013-14 and 2014-15. The performance evaluation of selected methods was carried out using linear regression and simple statistical analysis. The Most suitable method was compared with the methods reported for the various hilly and plain regions of the north India to suggest a substitute of PENMON method for estimation of reference evapotranspiration using minimal climatic parameters which are easily available. It was observed that the Penman method performed the best for hilly as well as for the plain regions and was in line with estimated ET0 by PENMON method with coefficient of determination (R2) of 0.95 and 0.89 and root mean square error (RMSE) 0.60 mm day-1 and 0.58 mm day-1 during 2013-14 and 2014-15, respectively. However, as compared to plain regions the value of ET0 estimated by Penman method was observed to be less for the hilly regions. Moreover, the Penman method requires only daily mean temperature, wind speed, air pressure, and solar radiation data.